Electronic FRAIL score may predict treatment outcomes in older adults with myeloma. Issue 4 (May 2021) - Chan, Henry; Chong, Yih Harng; Seow, Min Yee; Li, Jian; Garg, Priya; Kelly, Meaghan; Neylon, Annette; McDiarmid, Bridgett; Tan, Sarah; Jackson, Sharon
Abstract: Introduction: Frailty is a known risk factor for older patients with myeloma. Here we present realworld data using a computer-generated frailty assessment score (FRAIL score), based on 5 clinically derived parameters, in predicting patient outcomes. Methods: Older patients with newly diagnosed multiple myeloma who received frontline treatment with cyclophosphamide-bortezomib-dexamethasone had their FRAIL score retrospectively assessed. Treatment outcomes were assessed using standard IMWG criteria, and event free survival and overall survival determined. Results: 155 patients were analysed. Compared to those who were assessed as non-frail (FRAIL score 0–1) likely-frail patients (score ≥ 2) were less likely to complete the full course of treatment (24.3% vs 53.4%, p  = 0.002), and more likely to terminate treatment due to toxicities (35.1% vs 22.0%, p  = 0.109), as well as having a greater number of patients stop treatment early for reasons other than toxicity or progression (27.0% vs 10.2%, p  = 0.010). After a median follow up of 42.5 months, likely-frail patients were found to have a trend for shorter event-free survival (median EFS, 8.7 vs 17.9 months, p  = 0.064) and statistically inferior overall survival (median OS, 30.2 vs 49.8 months, p  < 0.001). After adjusting for age, stage, and Charlson comorbidity index, FRAIL score was prognostic for OS (HR = 3.47, 95% CI 1.88–6.4), but not EFS (HR = 1.28, 95%CI 0.79–2.06). Conclusion: The FRAIL score is independently predictive of overall survival in older patients with myeloma receiving bortezomib-based induction chemotherapy and can help identify those patients more likely to experience treatment toxicity.